Optical System With Brightness Amplification for Monitoring the Combustion of Aluminum-Based Nanopowders; IEEE Transactions on Instrumentation and Measurement; Vol. 69, iss. 2 - Li Lin; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Smirnov A. Andreas; Gubarev F. A. Fedor Aleksandrovich (2020, 2020)
Title screen